Mitochondrial DNA Variation Among Populations of Rhynchophorus ferrugineus (Coleoptera: Curculionidae) From Pakistan. Issue 1 (22nd September 2016) - Yasin, Muhammad; Rugman-Jones, Paul F.; Wakil, Waqas; Stouthamer, Richard
Abstract: The Red Palm Weevil (RPW) Rhynchophorus ferrugineus (Olivier) is a voracious pest of palm species. In recent decades its range has expanded greatly, particularly impacting the date palm industry in the Middle East. This has led to conjecture regarding the origins of invasive RPW populations. For example, in parts of the Middle East, RPW is commonly referred to as the "Pakistani weevil" in the belief that it originated there. We sought evidence to support or refute this belief. First reports of RPW in Pakistan were from the Punjab region in 1918, but it is unknown whether it is native or invasive there. We estimated genetic variation across five populations of RPW from two provinces of Pakistan, using sequences of the mitochondrial cytochrome oxidase subunit I gene. Four haplotypes were detected; two (H1 and H5) were abundant, accounting for 88% of specimens across the sampled populations, and were previously known from the Middle East. The remaining haplotypes (H51 and H52) were newly detected (in global terms) and there was no geographic overlap in their distribution within Pakistan. Levels of haplotype diversity were much lower than those previously recorded in accepted parts of the native range of RPW, suggesting that the weevil may be invasive in Pakistan. The affinity of Pakistani haplotypes to those reported from India (and the geographical proximity of the two countries), make the latter a likely "native" source. With regards the validity of the name "Pakistani weevil", we found little genetic evidence to justify it.